The Construction of Legal Liability in General Theory of Law(A Formulation of the Problem) - Igor' A. Kuz'min (Сибирское юридическое обозрение, 2017)
The article examines the legal nature of the construction of legal liability. A low level of doctrinal elaboration of “legal construction" category is noted. Based on analysis of issues and doctrinal positions the Author comes to a conclusion about the importance of further study of the construction of legal liability and denotes the criteria of scientific research and practical application of the construction of liability in law